5D Yang-Mills instantons from Aharony-Bergman-Jafferis-Maldacena monopoles - Lambert, N.; Nastase, H. [UNESP]; Papageorgakis, C. (American Physical Society (APS), 2012)
In the presence of a background supergravity flux, N M2-branes will expand via the Myers effect into M5-branes wrapped on a fuzzy 3-sphere. In previous work the fluctuations of the M2-branes were shown to be described by the five-dimensional Yang-Mills gauge theory associated to D4-branes. We show that the Aharony-Bergman-Jafferis-Maldacena prescription for 11-dimensional momentum in terms of magnetic flux lifts to an instanton flux of the effective five-dimensional Yang-Mills theory on the sphere, giving an M-theory interpretation for these instantons. © 2012 American Physical Society.